Pengaruh Tingkat Suku Bunga Kredit dan Jumlah Nasabah Terhadap Profitabilitas pada KBPR Bumi Arta - Yuliana Yuliana; Dwi Ari Pertiwi (Prodi Akuntansi Fakultas Ekonomi Universitas Hasyim Asy'ari, 2020)
Rural Banks are one of the banking financial institutions that collect funds from the public in the form of deposits and redistribute them in the form of credit,This research was conducted at KBPR Bumi Arta located on Jl. Irian Jaya No. 25 Cukir, Jombang.The purpose of this study was to determine the effect of credit interest rates and the amount of profit on profitability in KBPR Bumi Arta.This type of research is quantitative research.The population in this report is the financial report and KBPR Bumi Arta report for the last 5 years from 2013-2017 which discusses 60 research data.The sampling technique uses non-probability sampling using saturated samples,The sample used is the monthly financial statements, income statement, and KBPR Bumi Arta loan list report for the period 2013-2017.Data analysis techniques are multiple regression techniques,The results of the study show that the variable credit interest rate has a significant positive effect on the variable profitability, While the number of respondents has a significant effect on the variable profitability.